Bone marrow mesenchymal stem cell-derived exosomal lncRNA KLF3-AS1 stabilizes Sirt1 protein to improve cerebral ischemia/reperfusion injury via miR-206/USP22 axis - Xiaowei Xie; Yu Cao; Liangping Dai; Dingzhou Zhou (BMC, 2023)
Abstract Background Cerebral ischemia/reperfusion (I/R) is a pathological process that occurs in ischemic stroke. Bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) have been verified to relieve cerebral I/R-induced inflammatory injury. Hence, we intended to clarify the function of BMSC-Exos-delivered lncRNA KLF3-AS1 (BMSC-Exos KLF3-AS1) in neuroprotection and investigated its potential mechanism. Methods To mimic cerebral I/R injury in vivo and in vitro, middle cerebral artery occlusion (MCAO) mice model and oxygen-glucose deprivation (OGD) BV-2 cell model were established. BMSC-Exos KLF3-AS1 were administered in MCAO mice or OGD-exposed cells. The modified neurological severity score (mNSS), shuttle box test, and cresyl violet staining were performed to measure the neuroprotective functions, while cell injury was evaluated with MTT, TUNEL and reactive oxygen species (ROS) assays. Targeted genes and proteins were detected using western blot, qRT-PCR, and immunohistochemistry. The molecular interactions were assessed using RNA immunoprecipitation, co-immunoprecipitation and luciferase assays. Results BMSC-Exos KLF3-AS1 reduced cerebral infarction and improved neurological function in MCAO mice. Similarly, it also promoted cell viability, suppressed apoptosis, inflammatory injury and ROS production in cells exposed to OGD. BMSC-Exos KLF3-AS1 upregulated the decreased Sirt1 induced by cerebral I/R. Mechanistically, KLF3-AS1 inhibited the ubiquitination of Sirt1 protein through inducing USP22. Additionally, KLF3-AS1 sponged miR-206 to upregulate USP22 expression. Overexpression of miR-206 or silencing of Sirt1 abolished KLF3-AS1-mediated protective effects. Conclusion BMSC-Exos KLF3-AS1 promoted the Sirt1 deubiquitinating to ameliorate cerebral I/R-induced inflammatory injury via KLF3-AS1/miR-206/USP22 network.